Sentinel node (SLN) biopsy in the management of locally advanced cervical cancer - Cibula, David; Kužel, David; Sláma, Jiří; Fischerová, Daniela; Dundr, Pavel; Freitag, Pavel; Zikán, Michal; Pavlišta, David; Tomancová, Věra (Gynecologic oncology, 2009)
OBJECTIVES: Sentinel lymph node (SLN) biopsy can significantly contribute to the management of locally advanced cervical cancers with high risk of lymph node (LN) positivity. However, low detection rate and sensitivity were reported in larger tumors, albeit on a small number of cases. It was the aim of our study to verify the SLN reliability in large tumors, with modified dye application technique and a careful identification of side-specific lymphatic drainage. METHODS: The study involved 44 patients with tumors 3 cm in diameter or larger, stages IB1 to IIA, or selected IIB. In cases where SLN could not be detected, systematic pelvic lymphadenectomy was performed on the respective side. Systematic pelvic lymphadenectomy was performed during the second step radical procedure if not already done. RESULTS: Detection rate in the whole cohort reached 77% per patient and 59% bilaterally. No significant difference was found whether a blue dye or a combined method was used (75% vs 80%, and 55% vs 67%). Systematic pelvic lymphadenectomy was performed in cases with undetected SLN unilaterally in 8 and bilaterally in 10 women. A systematic pelvic lymphadenectomy was included in the second step radical procedure in 19 cases and no positive LN were found. There was no case of false-negative SLN result in patients who underwent surgical treatment. CONCLUSION: Detection rate in locally advanced cervical cancer could be improved by a careful dye application technique. Low false-negative SLN rate could be achieved if pelvic lymphatic drainage is evaluated on a side-specific principle by performing systematic lymphadenectomy if SLN is not detected.
Keywords: Coloring Agents; Young Adult; lymfatické uzliny; Lymph Node Excision; mladý dospělý; Lymph Nodes; Uterine Cervical Neoplasms; Neoplasm Staging; nádory děložního čípku; Rosaniline Dyes; Adult; lymfadenektomie; Aged; dospělí; laparoskopie; senioři; biopsie sentinelové lymfatické uzliny; lidé středního věku; falešně pozitivní reakce; lidé; ženské pohlaví; barvicí látky; Humans; Laparoscopy; Female; False Positive Reactions; staging nádorů; rosanilinová barviva; Sentinel Lymph Node Biopsy; Middle Aged